Voter information campaigns and political accountability: Cumulative findings from a preregistered meta-analysis of coordinated trials - Thad Dunning; Guy Grossman; Macartan Humphreys; Susan D. Hyde; Craig McIntosh; Gareth Nellis; Claire L. Adida; Eric Arias; Clara Bicalho; Taylor C. Boas; Mark T. Buntaine; Simon Chauchard; et al. (Science Advances, 2019)
Voters may be unable to hold politicians to account if they lack basic information about their representatives' performance. Civil society groups and international donors therefore advocate using voter information campaigns to improve democratic accountability. Yet, are these campaigns effective? Limited replication, measurement heterogeneity, and publication biases may undermine the reliability of published research. We implemented a new approach to cumulative learning, coordinating the design of seven randomized controlled trials to be fielded in six countries by independent research teams. Uncommon for multisite trials in the social sciences, we jointly preregistered a meta-analysis of results in advance of seeing the data. We find no evidence overall that typical, nonpartisan voter information campaigns shape voter behavior, although exploratory and subgroup analyses suggest conditions under which informational campaigns could be more effective. Such null estimated effects are too seldom published, yet they can be critical for scientific progress and cumulative, policy-relevant learning.
Keywords: 330